Job Satisfaction Mediates the Effects of Competence and Work Overload on Sustainable Assessor Performance - Maulana, Achmad; Widigdo, Aslam Mei Nur (International Journal of Law Policy and Governance, 2026)
Purpose – This study examines the influence of competence and work overload on the performance of sustainability assessors and analyses the mediating role of job satisfaction at PT SKP Tenaga Listrik. This study supports the achievement of Sustainable Development Goals (SDGs) 4, 7 and 8 through sustainable human resource management. Methodology/approach – This study employed a quantitative causal design, involving all 88 assessors through saturation sampling. Data were collected using a questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Findings – Competence and job satisfaction have a positive and significant effect on assessors’ sustainable performance. Conversely, excessive workload has a negative and significant effect on assessors’ sustainable performance and job satisfaction. Job satisfaction also mediates the effects of competence and excessive workload on assessors’ sustainable performance. These findings suggest that assessors’ performance can be sustainably improved through competence development, a proportionate distribution of workload, and increased job satisfaction. Novelty/value – This study develops an integrated model of assessors’ sustainable performance in the electrical sector’s competence certification sector, positing job satisfaction as a mediating mechanism linking competence and excessive workload to performance. The study’s findings provide a practical basis for the formulation of policies on competence development, workload management and the improvement of assessors’ wellbeing